KEBERSANAN MODUL PEMBELAJARAN DENGAN PENGGUNAAN PENDEKATAN KONSEPTUAL ENTERAKTIF BERBASIS PERALATAN BUDAYA TRADISIONAL UNTUK MENGURANGI MISKONSEPSI PELAJAR (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis study aimed to test the effectiveness of module Conceptual Approach in based traditional culture equipment to reducing misconceptions in students of Physics. The module is using ADDIE Model, Data necessary about student misconceptions in physics learning using examination before and after The implementation approaches. To conduct the study, involving all the students of class VIII Junior High School (SMP) Kuok, Kampar district, Riau as population. While the sample was taken at random from the population used Homogeneity and Normality Test, which is a school in the city and one rural school. The information obtained from the questionnaires were analyzed descriptive statistics and statistical inference. Descriptive analysis was used to examine the frequency, mean and percentage. While inferential analysis was used to hypothesis test. The Hypotheses were tested using t-tests comparing the mean and variance analysis (ANOVA) at 0.05 significant level as a guide for acceptance or rejection. The information presented only the essence or summary of computer output. The results showed that: (1) Misconceptions on groups of students in the city showed that in the pre-test of the experimental group which is equal to (mean = 2.498), while the control group of (min 2.4984), whereas in the group of students who were in rural in a pre-test of the experimental group which is equal to (mean = 2.2880), while the control group was 2.2668 is lower than the experimental group. (2) The misconceptions of force is still grouth are as followed concept of force, Newtons laws, work and energy and simple machines (3) The results of hypothesis testing showed that group of students in the city in experimental class group by PEKONSI BPBT learning, the average in the post-test (mean = 3.3488) were higher than average in the post-test control group (mean = 3.1340). while in the group of students in rural areas shows that in the experimental group classes by PEKONSI learning, misconceptions in the post-test (mean =Volume 2Proceeding: 7th International Seminar on Regional Education, November 5-7, 20157263.2952) is higher than the average in the post-test control (mean = 2.9460 ). This was showed that the teaching used PEKONSI BPBT learning can reduce students misconceptions more than the PEKONSI learning.Keywords: interactive conceptual approach, traditional culture equipment, Misconceptions, Force and application